2022
DOI: 10.7759/cureus.24116
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty of a Charcot Knee in a Patient With Congenital Insensitivity to Pain

Abstract: Hereditary sensory and autonomic neuropathies (HSANs) include hereditary disorders that cause congenital insensitivity to pain. Moreover, patients diagnosed with such disorders are known to have genetic mutations that alter their deep pain sensation, making them more prone to developing bone and joint complications such as repetitive fractures, joint swelling, and Charcot arthropathy. Neuropathic arthropathy (Charcot joint) is a rare and relatively poorly understood condition; it is suggested to be caused by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Four cases were treated surgically, two of which were treated by osteotomy and orthopedic approach 10,13 , one by lesion debridement 11 , and one by total knee arthroplasty. 12 In a short period of time, all of the above treatments showed limb function was signi cantly improved in all patients. However, at follow-up, the overall total postoperative complication rate requiring reoperation in these reported cases was 66.7% (Two cases were not reported with complications).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Four cases were treated surgically, two of which were treated by osteotomy and orthopedic approach 10,13 , one by lesion debridement 11 , and one by total knee arthroplasty. 12 In a short period of time, all of the above treatments showed limb function was signi cantly improved in all patients. However, at follow-up, the overall total postoperative complication rate requiring reoperation in these reported cases was 66.7% (Two cases were not reported with complications).…”
Section: Discussionmentioning
confidence: 86%
“…Although the surgical treatment of CN combined with CIPA remains controversial, several previous studies have reported on the e cacy of other surgical modalities in speci c cases. [10][11][12][13] As shown in Table 1, these reports describe various treatment procedures in patients with varying severity of CIPA with joint involvement in CN and differing outcomes. Four cases were treated surgically, two of which were treated by osteotomy and orthopedic approach 10,13 , one by lesion debridement 11 , and one by total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Rotating hinge prosthesis could provide better three‐dimensional freedom, and has been more frequently chosen for TKA to treat Charcot knee in the last 10 years (Figure 2 ). 20 , 21 Recently, more studies 5 , 6 , 9 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 reported the use of condylar constrained prostheses and rotating hinge prostheses with satisfied results for TKA in Charcot knee.…”
Section: Discussionmentioning
confidence: 99%
“…We present an unusual case of a patient with congenital pain insensitivity. Congenital pain insensitivity is a group of hereditary sensory and autonomic neuropathies [18][19][20] known to result in multiple musculoskeletal complications including multiple fractures, joint subluxation, and Charcot arthropathy [21][22][23][24] . As a result of his pain insensitivity, he required bilateral below-knee amputations and subsequently underwent bilateral osseointegration limb reconstructions.…”
Section: T He Incidence Of Lower-limb Amputation In the Unitedmentioning
confidence: 99%